2008
DOI: 10.1186/bf03352878
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic fault model of the 2008 Iwate-Miyagi Nairiku earthquake deduced by a dense GPS network

Abstract: A large earthquake of M j 7.2 occurred on June 14, 2008, beneath the border between Iwate and Miyagi prefectures in northeastern Japan. We propose a simple rectangular fault model based on a dense GPS network, including continuous GPS sites run by four agencies, to describe the coseismic deformation. The coseismic displacements are estimated by kinematic PPP (precise point positioning) analysis. Near the hypocenter, colocated independent instruments (integrated accelerogram and kinematic PPP) measure the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 13 publications
5
69
0
Order By: Relevance
“…This westward dipping aftershock alignment is thought to be along the major fault plane of the mainshock, as suggested by the GPS observation (cf. Ohta et al, 2008). Note that "eastward" dipping aftershock alignment can be seen in the vicinity of the main shock ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This westward dipping aftershock alignment is thought to be along the major fault plane of the mainshock, as suggested by the GPS observation (cf. Ohta et al, 2008). Note that "eastward" dipping aftershock alignment can be seen in the vicinity of the main shock ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The area in which the largest slip occurred during the mainshock (e.g. Ohta et al, 2008), as will be discussed in more detail later, extends for 15-20 km SSW from the hypocenter of the mainshock, at a shallow depth. The aftershocks occurred in an area that was significantly elongated in the N-S direction compared to the major slip area of the mainshock.…”
Section: Resultsmentioning
confidence: 99%
“…The aftershock plane coincides with the deeper extension of the range-bounding fault estimated by Abe et al (2008). GPS observation revealed that the upper edge of the coseismic fault was located several kilometers west of the surface trace of the Dedana fault, which is the southern part of the western marginal faults of the Kitakami lowland (Ohta et al, 2008). These results indicate that, in the northern part of the focal area, the 2008 Iwate-Miyagi Nairiku Earthquake occurred along the range-bounding fault, which is located at the eastern margin of the Ou backbone range.…”
Section: Resultsmentioning
confidence: 63%
“…On the basis of the heights of fluvial/marine terraces, Tajikara and Ikeda (2005) and Tajikara et al (2009) pointed out that the blind faults may be located at the topographical boundary between a range and a basin, where the active faults have not been mapped. On the basis of GPS measurements, Ohta et al (2008) revealed that no coseismic slip was estimated at the deeper extension of the Dedana fault. The upper edge of the coseismic fault deduced from a GPS observation was located several kilometers west of the surface trace of the Dedana fault (Ohta et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation